2015
DOI: 10.1089/omi.2015.0105
|View full text |Cite
|
Sign up to set email alerts
|

Novel Vaccine Candidates against Brucella melitensis Identified through Reverse Vaccinology Approach

Abstract: Global health therapeutics is a rapidly emerging facet of postgenomics medicine. In this connection, Brucella melitensis is an intracellular bacterium that causes the zoonotic infectious disease, brucellosis. Presently, no licensed vaccines are available for human brucellosis. Here, we report the identification of potential vaccine candidates against B. melitensis using a reverse vaccinology approach. Based on a systematic screening of exoproteome and secretome of B. melitensis 16 M, we identified eight protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…13,19 It has been established that T and B lymphocytes act as antigenic determinants or epitopes of antigens instead of entire antigens. T cell recognizes epitopic peptides using T cell receptor that binds to either MHC I (CD8 + T cell) or MHC II (CD4 + T cells) class molecules or both present on antigen-presenting cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,19 It has been established that T and B lymphocytes act as antigenic determinants or epitopes of antigens instead of entire antigens. T cell recognizes epitopic peptides using T cell receptor that binds to either MHC I (CD8 + T cell) or MHC II (CD4 + T cells) class molecules or both present on antigen-presenting cells.…”
Section: Resultsmentioning
confidence: 99%
“…We choose the threshold value of 0.4 to increase the accurate antigenicity and to avoid false-positive results. 19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several chimeric DNA vaccines have been designed to encode proteins omp19, omp31 and urease [154], BP26, omp31 and TF [155], and GroEL [156]. Based on systematic screening of the exoproteome and secretome of B. melitensis, Vishnu et al [157] identified eight proteins as potential vaccine candidates, including LPS-assembly protein LptD, a polysaccharide export protein, a cell surface protein, heme transporter BhuA, flagellin FliC, 7-alpha-hydroxisteroid dehydrogenase, immunoglobulin-binding protein EIBE, and hemagglutinin. Several B-and T-cell epitopes were predicted, and also from the protein omp25 [158].…”
Section: Prediction Of Immunogens For Veterinary Medicinementioning
confidence: 99%
“…Brucellosis can affect humans as well as many animals [1]. The prevalence of brucellosis has been observed Abbreviations: IMB, immune magnetic beads; QDs, quantum dots; SPA, staphylococcal protein A; ROC, receiver-operating characteristic; CI, confidence interval; CDC, Center for Disease Control and Prevention; RBPT, the Rose Bengal plate test; PAT, plate agglutination test; SAT, standard tube agglutination test; CFT, complement fixation test; ELISA, enzyme-linked immunosorbent assay; S-LPS, smooth lipopolysaccharides; PCR, Polymerase Chain Reaction; MNPs, magnetic nanoparticles; OMP, outer membrane protein; MES, 2-Morpholinoethanesulfonic Acid; EDC, N1-((ethylimino)methylene)-N3,N3-dimethylpropane-1,3-diamine; NHS, Nhydroxysuccinimide; TMB, 3,3 ,5,5 -Tetramethylbenzidine; BSA, albumin from bovine serum; OD, optical density; AUC, area under the ROC curve; E. coli O157:H, Escherichia coli O157:H7; LM, Listeria monocytogenes; CV, coefficient of variation; PL intensity, photoluminescence intensity.…”
Section: Introductionmentioning
confidence: 99%